IMPACT OF SPECIALIZED AND UNSPECIALIZED PHYSICAL EDUCATION TEACHERS ON THE SPEED AND ENDURANCE OF 7-9-YEAR-OLD STUDENTS - Kornelia Naydenova (Scientific Publishing House. NSA Press, 2023)
Reduced motor activity and impaired physical fitness are among the great problems of modern society. Many authors point out that one solution to this problem is creating a lasting interest in motor activity before the age of 10-11 when the child has a natural need for movement. At the same time, in Bulgaria and many other countries, physical education in preschool and primary school age is taken over by teachers who are not specialists in physical education and sports. This study aimed to track changes in acquiring motor abilities such as speed and endurance for pupils in the 1st, 2nd, and 3rd grades, aged 7 to 9 years, with whom specialists with different specializations have worked. The research was carried out with 11 pupils at a primary school. Running 30 m and Shuttle Running 4 x 50 m tests were used. The testing and mathematical-statistical methods (variation analysis and comparative analysis with t-criterion of Student) were used in the study. The analysis showed a significant difference in students' results between physical education and non-specialist teacher training. Undoubtedly, training by a non-specialist teacher leads to a decrease in the values of the considered indicators in the pupils' physical fitness.